2021
DOI: 10.1177/14614448211027171
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the learning potential of online gaming communities: An application of the Game Communities of Inquiry Scale

Abstract: Online gaming is becoming increasingly social and interconnected. Millions of players learn from each other in game-related communities on platforms like Reddit and Twitch.tv. However, few studies have been conducted to examine socially constructed learning in such environments. The purpose of this study was to explore learning in game-related communities using the Game Community of Inquiry Scale (GCoIS). GCoIS is a validated instrument inspired by the community of inquiry framework and developed for measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
1
12
0
2
Order By: Relevance
“…In addition, the ability of a community to be open and inclusive is a key factor in fostering cognitive processes. This highlight matches previous funding related to these groups and their main attitudes (Gandolfi et al, 2021). Finally, age, gender, ethnicity, and type of platform were not predictors of CC, suggesting that these communities may be more inclusive than what other studies have suggested (e.g., Euteneuer, 2019; Yen et al, 2020).…”
Section: Playing Beyond Gamingsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, the ability of a community to be open and inclusive is a key factor in fostering cognitive processes. This highlight matches previous funding related to these groups and their main attitudes (Gandolfi et al, 2021). Finally, age, gender, ethnicity, and type of platform were not predictors of CC, suggesting that these communities may be more inclusive than what other studies have suggested (e.g., Euteneuer, 2019; Yen et al, 2020).…”
Section: Playing Beyond Gamingsupporting
confidence: 89%
“…However, there are also opportunities for individuals to bond with and learn from each other. Indeed, preliminary evidence shows that game outlets can be proactive environments where community and educational instances may take place (Gandolfi et al, 2021; Pearce, 2011). Moreover, online gaming and related social engagement have been related to positive and inclusive learning experiences (Jung, 2020a; Squire, 2010), where problem solving and critical thinking are promoted in a shared environment (Hau & Kim, 2011).…”
Section: Expanding the Educational Impact Of Video Gamesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ello se debe a los cambios en los procesos de educación, que requieren cada vez procesos más dinámicos de interacción entre los participantes en el proceso, aspectos vitales para promover la generación de nuevo conocimiento y una mejor motivación, y que se instrumentan además en procesos de aprendizaje continuo y autodirigido para toda la vida, que tienen cada vez más cabida y relevancia en el campo educativo (Garrigós et al, 2019;Montesa et al, 2014) Dadas estas potencialidades, el uso y potencial de Twitch en educación ha sido explorado en la literatura por autores como Payne et al, (2017Payne et al, ( , 2019 o Pirke et al (2021). A ello deberíamos añadir la relevancia de esta red para mejorar la investigación (Carradore y Carrera, 2019), desarrollar, actualizar y promover el aprendizaje de profesores , incrementar y elevar el aprendizaje autodirigido (Blaschke, 2012), como instrumento complementario del aprendizaje invertido o Flipped learning (Pozo-Sánchez et al (2021), como herramienta para aumentar la accesibilidad en la educación y eliminar las barreras de personas con discapacidad (Johnson (2019), para la obtención y generación de contenidos por y para los alumnos Sjoblom et al (2017), para la mejora del aprendizaje del alumno Llorente et al (2015;Gandolfi et al 2021), tanto directamente como a través de la mejora de su motivación Sjoblom et al (2017), Hilvert-Bruce et al (2018), Chou y Lu (2021), o para el desarrollo la mejora del aprendizaje continuo y autodirigido para toda la vida Staudt Willet, y Carpenter, J. P. (2021) .…”
Section: Historia Y Características De Twitch Y Su Uso En Educaciónunclassified